2006
DOI: 10.2139/ssrn.823504
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Information, Disclosure, and the Cost of Capital

Abstract: In this paper we examine whether and how accounting information about a firm manifests in its cost of capital, despite the forces of diversification. We build a model that is consistent with the Capital Asset Pricing Model and explicitly allows for multiple securities whose cash flows are correlated. We demonstrate that the quality of accounting information can influence the cost of capital, both directly and indirectly. The direct effect occurs because higher quality disclosures affect the firm's assessed cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
863
2
46

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 649 publications
(949 citation statements)
references
References 38 publications
38
863
2
46
Order By: Relevance
“…Theory posits that higher quality and more comparable accounting information can reduce information asymmetry and estimation risk (for detailed discussions, see Dye 1990;Verrecchia 2001;Easley and O'Hara 2004;and Lambert et al 2007). Consistent with theory, prior empirical studies have confirmed the role of financial statement information in mitigating agency costs in a debt-financing context.…”
Section: Theory and Related Literaturementioning
confidence: 87%
“…Theory posits that higher quality and more comparable accounting information can reduce information asymmetry and estimation risk (for detailed discussions, see Dye 1990;Verrecchia 2001;Easley and O'Hara 2004;and Lambert et al 2007). Consistent with theory, prior empirical studies have confirmed the role of financial statement information in mitigating agency costs in a debt-financing context.…”
Section: Theory and Related Literaturementioning
confidence: 87%
“…12 As of December 31, 2008, 763 companies were listed on the Korea Stock Exchange and 1,036 companies were listed on the KOSDAQ. 13 Prior studies speculate that, in general, the companies that are listed in emerging countries have a higher cost of equity capital due to (1) a weaker financial system (Chang, 2005), (2) poor corporate governance (Baek et al, 2004(Baek et al, , 2009Hail and Leuz, 2006), and (3) lack of BE including corporate transparency (Baek et al, 2004;Botosan, 1997;Botosan and Plumlee, 2002;Choi and Jung, 2008;Choi and Nakano, 2008;Dargenidou et al, 2006;Habib, 2006;Lambert et al, 2007;Poshakwale and Courtis, 2005). 14 Pearson and Kendall's s-b correlations were also tested.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that voluntary IFRS adoption reduces borrowing costs. Lambert et al (2007) provide another reason why high-quality information reduces the cost of external financing. Their analysis indicates that high-quality reports improve coordination between firms and capital suppliers with respect to capital investment decisions, while poor-quality reports lead to misaligned capital investments due to impaired coordination.…”
Section: The Effect Of Ifrs Adoption On Borrowing Ratesmentioning
confidence: 99%